Gastrointestinal Symptoms in Morbid Obesity - Huseini, Mustafa; Wood, G. Craig; Seiler, Jamie; Argyropoulos, George; Irving, Brian A.; Gerhard, Glenn S.; Benotti, Peter; Still, Christopher; Rolston, David D. K. (Frontiers in Medicine, 2014)
Background: Several reports have shown an increased prevalence of gastrointestinal (GI) symptoms in obese subjects in community-based studies. To better understand the role of the gastrointestinal tract in obesity, and because there are limited clinic-based studies, we documented the prevalence of upper and lower GI symptoms in morbidly obese individuals in a clinic setting Objective The aim of our study was to compare the prevalence of gastrointestinal symptoms in morbidly obese individuals in a weight management clinic with non-obese individuals with similar comorbidities as morbidly obese individuals in an Internal Medicine clinic. Methods Class II and III obese patients BMI>35 kg/m2 (n = 114) and 182 non-obese patients (BMI <25kg/m2) completed the GI symptoms survey between August 2011 and April 2012 were included in this study. The survey included 24 items pertaining to upper and lower GI symptoms. The participants rated the frequency of symptoms as absent (never, rarely) or present (occasionally, frequently). The symptoms were clustered into five categories: oral symptoms, dysphagia, gastroesophageal reflux, abdominal pain, bowel habits. Responses to each symptom cluster were compared between obese group and normal weight groups using logistic regression. Results Of the 24 items, 18 had a higher frequency in the obese group (p<0.005 for each). After adjusting f(1)or age and gender, the obese patients were more likely to have upper GI symptoms: any oral symptom (OR = 2.3, p=0.0013), dysphagia (OR 2.9, p=0.0006), and any gastroesophageal reflux (OR 3.8, p<0.0001). Similarly, the obese patients were more likely to have lower GI symptoms: any abdominal pain (OR=1.7, p=0.042) and altered bowel habits (OR=2.8, p<0.0001). Conclusion These observations suggest a statistically significant increase in frequency of both upper and lower GI symptoms in morbidly obese patients when compared to non-obese subjects.